Influencia de la edad de reproductoras de la línea cobb 500 sobre la incubabilidad del huevo evaluado a través de embriodiagnosis - Escobedo Rámirez, Mónica Carolina (2013)
The present investigation was carried out by the aim to evaluate the influence of age of breeders Cobb line 500 on the egg hatchability evaluated through embriodiagnosis in the plant of incubation of Investments Delma S.A.C of the District of Trujillo department of The freedom. To determine the parameters of the motive of study the following indicators were evaluated: hatchability, fertility, birth fertile eggs, chopped eggs unborn, contaminated eggs and embryonic mortality. 1818 eggs were analyzed for three 3-breeder flocks of different ages, 34, 45 and 60 weeks, those same lots was assessed one week of age corresponding to the age of 35, 46 and 61 weeks. To complete the process, extracted 3 shelves above, middle and down and lights out with a flashlight illuminating the upper pole of the eggs, those eggs are clear to light removed for evaluation meeting infertile eggs, mortality of first and second week, contaminated and other eggs in the trays were transferred to hatchers at 18 days and 21 days was performed obtaining embryonic mortality embriodiagnosis third week, chopped eggs unborn chickens born. For the analysis of the results we used the software Microsoft Excel 2007 and SPSS version 19.0, with the following results, the eggs from hens aged 34, 35 and 45, 46 consecutive weeks highest percentage of hatchability obtained with an average of 89% and 87% respetivamente, with statistically significant differences (p ≤ 0.05). The fertility rate averages obtained in the different ages of breeding, show no statistically significant differences (p ≤ 0.05). Averages of fertile hatchability obtained, showing the most value in the breeding group of 45 weeks and 34 weeks old respectively whose averages are 89% and 91% respectively, showing statistically significant differences (p ≤ 0.05). The average embryonic mortality in the first, second and third week, show no statistically significant differences (p ≤ 0.05). The averages of the percentage of contaminated eggs obtained in the first and second charge, showed no statistically significant differences (p ≤ 0.05)